2001
DOI: 10.1128/jvi.75.5.2435-2443.2001
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus Can Productively Infect Primary Human Keratinocytes and Alter Their Growth Properties

Abstract: Kaposi's sarcoma (KS) is a multicentric vascular neoplasm involving the skin and mucosal surfaces and in aggressive cases may involve visceral organs and lymph nodes. KS lesions contain distinctive proliferating spindle cells, activated endothelial cells, fibroblasts, smooth muscle cells, and infiltrating inflammatory cells (35,39). Four different epidemiologic forms of Kaposi's sarcoma have been described, i.e., the classic, endemic, iatrogenic, and AIDS-related forms (22, 47).The gamma-2 herpesvirus KSHV, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 51 publications
2
49
0
Order By: Relevance
“…The data are consistent with previous studies showing infection of epithelial cells derived from foreskin keratinocytes (3,9). Oral epithelial cell types ranging from primary to transformed were susceptible substrates.…”
Section: Discussionsupporting
confidence: 82%
“…The data are consistent with previous studies showing infection of epithelial cells derived from foreskin keratinocytes (3,9). Oral epithelial cell types ranging from primary to transformed were susceptible substrates.…”
Section: Discussionsupporting
confidence: 82%
“…25,26 Alteration of telomerase activity has been reported in cells infected with HIV and Kaposi's sarcoma-associated herpesvirus. [35][36][37] While HSV-1/2 are not considered carcinogenic, clinical correlation between HSV-2 and human carcinoma of cervix remains to be a debatable issue. [38][39][40][41][42][43][44][45][46] It is unclear whether the HSV-1-induced upregulation of telomerase activity showed in the present study could afford individual cell freedom from senescence, allow accumulations of the genetic changes and chromosome instability, and eventually lead to pathological state such as cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also have shown the presence of KSHV viral DNA in basal keratinocytes and epithelial cells surrounding and within the KS lesion (10,11). The detection of infectious viral particles in the saliva of KSHV-infected individuals has suggested that the epithelial cells in the oral mucosa or salivary glands are a source of the virus (12)(13)(14)(15), and it is thought that KSHV may infect epithelial cells in transit during initial infection (16). In tissue culture studies, KSHV is capable of infecting several types of cells, including human primary keratinocytes, B cells, and endothelial, epithelial, and fibroblast cells (17,18).…”
Section: Introductionmentioning
confidence: 99%